Effects of Dancesport on Walking Balance and Spin Balance of University Athletes at Shenzhen Technology University - Feng, Xiezhuoyi; Hongseanyatham, Prakit; Saochalerm, Achara (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Since walking balance and spin balance are considered crucial skills for dancesport athletes, whether they can perform well or not partially depends on having good postural stability skills or not. Therefore, this research aims to study the effects of dancesport on walking balance and spin balance of university athletes at Shenzhen Technology University, to improve walking balance and spin balance of university athletes. Materials and Methods: This research was quasi-experimental. The research population was university dancesport athletes, individuals possessing fundamental dance skills but not classified as professional athletes, with a total of 30 athletes. The sample group for this research encompasses the entire population, comprising 30 university dance sports athletes. In this experiment, the training will be conducted over a total of 8 weeks, with 5 days per week and 2 hours per day. In addition, there will be tests for walking balance and spin balance conducted a total of 3 times, which include (1) before the start of training; (2) after completing 4 weeks of training; and (3) after completing training in week 8. This study utilized mean, standard deviation, one-way repeated measures ANOVA, and dependent t-tests for data analysis, with the significance level established at 0.05. Results: After 8 weeks of training with the developed dancesport training program, there was a statistically significant improvement at the 0.05 level in walking balance and spin balance of university athletes. Conclusion: The developed dance sports training program was effective in improving the walking balance and spin balance of university athletes.